2019
DOI: 10.1159/000502788
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporin 107 Promotes the Survival of Tumor Cells in Cervical Cancers

Abstract: <b><i>Aims:</i></b> Recent studies indicate that in addition to the construction of nuclear pore complex, nucleoporin (NUP)107 is actively involved in the pathogenesis of numerous cancer types, but the role of NUP107 in cervical carcinoma cells remains unknown. <b><i>Methods:</i></b> We examined the expression of NUP107 in 30 cases of cervical carcinoma using quantitative reverse transcription-polymerase chain reaction and immunoblots. NUP107 stably overexpressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…NUP107 was also confirmed as a key regulator of the intra‐S‐phase checkpoint response, which is induced by DNA damage 46 . The role of NUP107 in cell proliferation may vary in different cell lines 47 . Although significant proliferation and apoptosis inhibition did not occur after knockdown of NUP107 , this might be because nucleoporin has considerable functional redundancy, as was previously reported 48 .…”
Section: Discussionmentioning
confidence: 58%
“…NUP107 was also confirmed as a key regulator of the intra‐S‐phase checkpoint response, which is induced by DNA damage 46 . The role of NUP107 in cell proliferation may vary in different cell lines 47 . Although significant proliferation and apoptosis inhibition did not occur after knockdown of NUP107 , this might be because nucleoporin has considerable functional redundancy, as was previously reported 48 .…”
Section: Discussionmentioning
confidence: 58%
“…For example, Shi et al demonstrated that the expression of NUP107 is significantly upregulated in cervical cancer samples and cell lines. Besides, overexpression of NUP107 promotes the sensitivity of cervical cancer cells to oxidative insults [ 43 ]. Alanee et al discovered that a single nucleotide variant in NUP107 might be predictive of chemosensitivity in ovarian cancer patients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…MELK expression was correlated with resistance of radiation and chemotherapy in colorectal cancer[108], as well as survival of patients with multiple cancer types [109][110][111].The clinical trials and basic experiments for cancers with MELK inhibitor are ongoing. The overexpression of NUP107 increased resistance to oxidative damage in cervical cancer [112]. Previous studies have indicated that DEPDC1B induces tumor cell proliferation, migration, invasion and metastasis through various mechanisms [113][114][115][116].…”
Section: Discussionmentioning
confidence: 99%